Evidence That Nine Autistic Women Out of Ten Have Been Victims of Sexual Violence - Cazalis, Fabienne; Reyes, Elisabeth; Leduc, Séverine; Gourion, David (Frontiers in Behavioral Neuroscience, 2022)
Background: Research indicates that sexual violence affects about 30% of women in the general population and between two to three times as much for autistic women. Material and methods: We investigated prevalence of sexual abuse, autistic traits and a range of symptoms, using an online survey addressed to the women of the French autistic community (n=225). We assessed victimization through an open question and through a specific questionnaire, derived from the Sexual Experiences Survey-Short Form Victimization. Results: Both case identification methods yielded high figures: 68.9% victimization (open question) compared to 88.4% (standardized questionnaire). Two thirds of the victims were very young when they were first assaulted: among 199 victims, 135 were aged 18 or below and 112 participants were aged 15 or below. 75% of participants included in our study reported several aggressions. Analyses indicate that primo-victimization was highly correlated to revictimization and that being young increased that risk. Young victims were also at higher risk of developing post-traumatic stress disorder. A third of the victims reported the assault. 25% of those were able to file a complaint (n=12) and/or receive care (n=13). For the remainder 75%, reporting did not lead to action. Discussion: Those findings indicate a very large proportion of victims of sexual assault among autistic women, consistently with previous research. The World Health Organization states unambiguously that sexual violence is systemic and that vulnerable individuals are preferably targeted by offenders. We therefore postulate that it would be erroneous to consider that victimization of autistic women is mainly due to autism. On the contrary, autism seems to be just a vulnerability factor. Some authors propose that educating potential victims to better protect themselves would help preventing abuse. We reviewed this proposition in the light of our results and found it to be impossible to apply since more than half of the victims were below the age of consent. Literature about sexual violence is discussed. Large-scale prevention programs proposed by World Health Organization and the Center for Disease Control aim at cultural changes in order to diminish gender inequality, that they identify as the very root of sexual violence.